(untitled) (Journal of Laboratory Animal Science, 2018)
Ever since the revival of the Prevention of Cruelty to Animals Act (1960 )in 1998, the law was amended and implemented with renewed vigor, the animal welfare and laboratory animal experimentation has seen a major change. The strict imple mentation of the law during the early part of the decade led to the spilling of skeletons from cupboards of some very well known and established institutions in India. The implemen tation of the law not only revealed the lack of basic facilities and poor and unhygienic conditions in animal facilities, it also revealed the laid back attitude of those who were responsible. The increase in awareness that was achieved through the animal welfare movement in India was enormous. It has led to the improvement of laboratory animal facilities in several institutions and the commissioning and constitution of Institutional Animal Ethics Committees (IAEC) in all the CPCSEA (Committee for the Purpose of Control and Supervision of Experiments on Animals), Animal Welfare Division, Ministry of Environment and Forests, Government of India, registered organizations. The IAEC is in turn playing a major role in improving the welfare of the animals used for experiments. Nevertheless, the improvement of animal facilities in the Pharmaceutical industry and the Contract Research Organizations (CRO) to this day are driven more by the need to attract and capture business than a true change in the heart for the welfare of animals. The race for acquiring Good Laboratory Practices and Association for Assessment and Accreditation of Laboratory Animal Care International (AAALAC International) accreditation in the private industry, and the contrasting laid back attitude in the Government sector as was evident before 1998 is a clear indication of this fact. It may also be considered here that the threat of the law and negative public opinion has played a significant effect on the Government Institutions and several of them did release funds and have improved the animal facilities in their respective organizations.